Off-line analysis in the manganese catalysed epoxidation of ethylene-propylene-diene rubber (EPDM) with hydrogen peroxide. Issue 51 (4th October 2021) - de Roo, C. Maurits; Kasper, Johann B.; van Duin, Martin; Mecozzi, Francesco; Browne, Wesley
Abstract : Epoxidation of ethylene-propylene-diene rubber (EPDM ), based on 5-ethylidene-2-norbornene, to epoxidized EPDM (eEPDM ) opens routes to cross-linking and reactive blending, with increased polarity aiding adhesion to polar materials such as silica. Abstract : The epoxidation of ethylene-propylene-diene rubber (EPDM ) with 5-ethylidene-2-norbornene (ENB ) as the diene to epoxidized EPDM (eEPDM ) creates additional routes to cross-linking and reactive blending, as well as increasing the polarity and thereby the adhesion to polar materials, e.g., mineral fillers such as silica. The low solubility of apolar, high molecular weight polymers in the polar solvents constrains the catalytic method for epoxidation that can be applied. Here we have applied an in situ prepared catalyst comprising a manganese(ii ) salt, sodium picolinate and a ketone to the epoxidation of EPDM rubber with hydrogen peroxide (H2 O2 ) as the oxidant in a solvent mixture, that balances the need for polymer and catalyst/oxidant miscibility and solubility. Specifically, a mixture of cyclohexane and cyclohexanone is used, where cyclohexanone functions as a co-solvent as well as the ketone reagent. Reaction progress was monitored off-line through a combination of Raman and ATR-FTIR spectroscopies, which revealed that the reaction profile and the dependence on the composition of the catalyst are similar to those observed with low molar mass alkene substrates, under similar reaction conditions. The combination of spectroscopies offers a reliable method for off-line reaction monitoring of both the extent of the conversion of unsaturation (Raman) and the extent of epoxidation (FTIR) as well as determining side reactions, such as epoxide ring opening and further, aerobic oxidation. The epoxidation of EPDM described, in contrast to currently available methods, uses a non-scarce manganese catalyst and H2 O2, and avoids side reactions, such as those that can occur with peracids.